Supervisi Akademik Sebagai Upaya Peningkatan Kemampuan Guru Mengembangkan Pendekatan Pembelajaran di SMAN 13 Pekanbaru - Abdul Gafar (Journal on Education, 2022)
This study aims to discuss and obtain information regarding the application of academic supervision to improve teachers' abilities to develop learning approaches at SMAN 13 Pekanbaru. This research is a school action research which consists of two cycles where each cycle follows four stages, namely planning, implementing, observing and reflecting. This research was conducted at SMAN 13 Pekanbaru in the even semester of the 2021/2022 school year with teachers at SMAN 13 Pekanbaru as the subject. Data collection techniques use observation sheets, field notes, and documentation. Data were analyzed using percentages and data reduction. The results of the study show that through academic supervision it can improve the ability of teachers to develop learning approaches at SMAN 13 Pekanbaru by giving rewards.